Karakteristik Bakteri yang Di Isolasi Dari Darah Rusa Timor (Cervus Timorensis) di Kota Kupang - Novianti Neliyani Toelle; Yanse Yane Rumlaklak (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2019)
Clostridium, a bacteria gram-positive and motile, has a rod-shaped that can produce spora. It is a bacteria pathogen if it is contained one or more type of toxins. Blood samples were taken from healthy breastfeeding Timoranses deer (Cervus timorenses) in Forestry Conversation Cage in Oil Sonbay, Kupang. The bloods were cultured in anaerob blood agar plate or Potato Agar Dextrose then incubated at 370 C temperature for 24-28 hours. The next tests were spora staining, catalase, oksidase, motil, Voges Proskauer (VP) and Indol test. The results of all tests showed that the bacteria in the blood samples were Clostridium spp.